Manajemen Krisis Bank Syariah Indonesia Dalam Membentuk Citra Positif - Muhammad Rafid Alfattah; Sa’diyah El Adawiyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
The establishment of a company or organization will definitely go through difficult times in its development. Difficult times that occur in a company are certainly undesirable because they can have a negative impact and endanger the sustainability of the company or organization. Public Relations who play a role in a company must have skills, namely crisis management, to make it easier to resolve crises that occur in the company. The purpose of this research is to determine the crisis management of Bank Syariah Indonesia in forming a positive image. The theory used in this research is Public Relations crisis management proposed by W. Timoothy Coombs, including pre-crisis, crisis response and post-crisis. This research approach is qualitative with descriptive methods. The data collection techniques used were interviews and observation. The results of this research show that crisis management carried out by Bank Syariah Indonesia went through 3 stages, namely pre-crisis, crisis response, and post-crisis. In the pre-crisis stage, it shows that Indonesian sharia banks prepare and identify crises by monitoring every day and when a crisis occurs or in the crisis response stage, Indonesian sharia banks continue to carry out monitoring activities plus mapping to develop strategies and tactics to use when a crisis occurs. After the crisis or post-crisis stage, Bank Syariah Indonesia held a communication summit to convey the vision and mission to internal parties to be better prepared to face the next crisis. By collaborating with brand ambassador Putri Ariani, Bank Syariah Indonesia encouraged internal parties with life stories from their brand ambassador. With the crisis that occurred, changes were made to Bank Syariah Indonesia where BSI was more enthusiastic in providing comfort and security to customers